PENGEMBANGAN LAHAN SAWAH (Sawah Bukaan Baru) DAN KENDALA PENGELOLAANNYA DALAM PENCAPAIAN TARGET SURPLUS 10 JUTA TON BERAS TAHUN 2014 - Chairul Muslim (Universitas Sebelas Maret, 2014)
Food is a strategic commodity, and food availability absolute priority because it can create food security and national stability. The purpose of the Director General of Food Crops is to maintain the availability of food. For 2014 the target is 10 million tons of Ministry of Agriculture surplus. In order to achieve this program certainly accompanied by inter-ministerial coordination, one with the ministry of Public Works, in order to improve the irrigation network. The purpose of this paper is to discuss the development of new wetland openings, and is limited to aspects of the development potential of land for opening new fields, as well as various technical constraints management opening new fields of socio-economic aspects. Period (1992-2002) wetland conversion to nonagricultural reached 110,000 ha per year. And in the time span 2007-2010, in Java, the average conversion rate of 200,000 ha per year in the form of land irrigated technical, nontechnical and dry land. New paddy fields is one form of change of use of land resources is not agricultural land into agricultural land. And targets are achieved during the period 2010 - 2014 is 2 million hectares. While the Ministry of Agriculture to plan targets new paddy fields in 2012 covering an area of 100,000 hectares (ha) outside Java. To realize the program tersbut still many obstacles that must be resolved, one of the obstacles which spatial and spatial policy in Indonesia has not had a consistent policy, and tend to overlap (vertically or horizontally). To overcome this problem one solution is the collaboration of all stakeholders, including government, private sector, researchers, farmers, and food industry players in strengthening national food security.